THE IMPACT OF PROBIOTICS ON THE GROWTH AND SOIL AND WATER QUALITY OF FRESHWATER FISH, Pangasius hypophthalmus AND Piaractus brachypomus (Proceedings International Conference on Fisheries and Aquaculture, 2025)
In aquatic farming, probiotic products are seen as an alternative to the use of antibiotics. In freshwater fishes can benefit from probiotic organisms in a number of ways, including increased growth, reduced pathogen colonization, improved nutrient digestion, improved soil and water quality, increased stress tolerance, improved feed utilization, and an increased survival rate. can benefit from probiotic organisms in a number of ways, including increased growth, reduced pathogen colonization, improved nutrient digestion, improved soil and water quality, increased stress tolerance, improved feed utilization, and an increased survival rate. Present study techniques to include the probiotic strains in the fish feed pellets to development of fish biochemical and digestive system and organic waste buildup degrades the quality of the soil and water, which inhibits the growth of freshwater fish in earthen ponds. In order to prevent this issue, a 90-day supplementation experimentation was carried out to ascertain the impact of commercial probiotics "Super-PS" on the maintenance of beneficial soil and water quality parameters as well as the development of Pangasius hypophthalmus and Piaractus brachypomus fish cultured in freshwater earthen ponds. There are numerous ways that probiotic bacteria can enhance the quality of soil and water. Rhodococcus and Rhodobacter species are combined in "Super-PS." During the culture period, a freshwater pond was treated with water probiotic "Super PS" for 15 lit/ha from 1 to 30 days, 30 lit/ha from 31 to 60 days, 40 lit/ha from 61 to 90 days, and 91 days, depending on the pond condition, stocking density, and culture days, until harvest. The factors responsible for the improved water quality and significant growth up to harvest fresh water fishes under the influence of soil and water probiotics was analysed and together with the digestive enzymes, biochemical composition and histologically confirmed.
Keywords: Rhodococcus; Rhodobacter; fresh water fishes; growth & soil & water quality